Polarizing film and its manufacturing method
Patent Information
- Application Number
- JP2021535331
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-29
- Filing Date
- 2020-07-27
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-07-27
AI Technical Summary
【0013】 本発明によれば、高温下での収縮力が小さく、光学性能にも優れた偏光フィルム、及びその製造方法を提供することができる。
Smart Images

Figure 0007610509000008 
Figure 0007610509000001 
Figure 0007610509000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing film and a method for producing the same. [Background technology]
[0002] Polarizing plates, which have the function of transmitting and blocking light, are the basic components of liquid crystal displays (LCDs) along with liquid crystals, which change the polarization state of light. Many polarizing plates have a structure in which a protective film such as a triacetate cellulose (TAC) film is laminated to the surface of the polarizing film to prevent the film from fading or shrinking. The polarizing film that constitutes the polarizing plate is a matrix of uniaxially stretched polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be referred to as "PVA") with an iodine-based dye (I 3‐ or I 5‐ The mainstream is those that adsorb
[0003] LCDs are used in a wide range of applications, including small devices such as calculators and wristwatches, smartphones, notebook computers, LCD monitors, LCD color projectors, LCD televisions, in-car navigation systems, and measuring instruments used indoors and outdoors. In recent years, these electronic devices have been required to be thinner and have higher definition. Accordingly, the glass used in LCDs has become thinner and polarizing films have become more highly stretched, resulting in the problem of LCD panel warping. It is said that the main cause of LCD panel warping is the shrinkage of polarizing films at high temperatures, and there is a demand for polarizing films that have high optical performance and small shrinkage force at high temperatures.
[0004] Incidentally, in recent methods for producing polarizing films, it is known that an aqueous solution of boronic acid is used to crosslink PVA molecular chains in the polarizing film. Specifically, Patent Document 1 describes that a polarizing film having excellent wet heat resistance was obtained by immersing a polarizing film after uniaxial stretching in an aqueous solution (fixing treatment bath) containing 1,4-butanediboronic acid and potassium iodide. Patent Document 2 describes that a polarizing film having excellent water resistance and adhesive strength was obtained by adding a boronic acid derivative group in the water washing stage. Patent Document 3 describes that a polarizing film having excellent heat resistance and wet heat resistance was obtained by using a crosslinking liquid containing a hydrocarbon compound having an aldehyde group. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2018 / 021274 [Patent Document 2] KR10-2016-0054229 publication [Patent Document 3] KR10-2015-0001276 publication Summary of the Invention [Problem to be solved by the invention]
[0006] However, the polarizing films described in Patent Documents 1 to 3 have either a large shrinkage force at high temperatures or insufficient optical performance, and therefore cannot meet the recent demand for thinner and higher-definition electronic devices.
[0007] Therefore, an object of the present invention is to provide a polarizing film which has a small shrinkage force at high temperatures and excellent optical performance, and a method for producing the same. [Means for solving the problem]
[0008] The inventors have made intensive studies and found that in order to reduce the contraction force while maintaining the excellent optical performance of the polarizing film, it is important to allow the substitution reaction of replacing the boric acid crosslinking the PVA molecular chain in the polarizing film with boronic acid to proceed not only to the surface of the polarizing film but also to the center in the thickness direction. It was also found that the more the substitution reaction proceeds to the center in the thickness direction of the polarizing film, that is, the more the boric acid in the center in the thickness direction of the polarizing film is replaced with boronic acid, the more the contraction force of the polarizing film is reduced. Therefore, the inventors have completed the present invention by setting the ratio of the concentration of boron element derived from boronic acid (boron-containing compound) and boric acid in the center in the thickness direction of the polarizing film to a specific range.
[0009] In addition, in order to allow the substitution reaction of replacing boric acid in the polarizing film with boronic acid to proceed to the center of the polarizing film in the thickness direction, it is important to immerse the boric acid crosslinked polarizing film in a relatively low concentration boronic acid aqueous solution. Usually, when the boric acid crosslinked polarizing film is immersed in a boronic acid aqueous solution, the substitution reaction of replacing boric acid in the polarizing film with boronic acid proceeds from the surface of the polarizing film. Here, when the concentration of the boronic acid aqueous solution is relatively high, boronic acid is excessively adsorbed on the surface of the polarizing film, making it difficult for the substitution reaction to proceed to the center of the polarizing film in the thickness direction. In addition, in such a case, there is a risk of boronic acid deposits being generated on the surface of the polarizing film. On the other hand, in the present invention, the boric acid crosslinked polarizing film is immersed in a relatively low concentration boronic acid aqueous solution, so that the substitution reaction can proceed to the center of the polarizing film in the thickness direction.
[0010] The present invention includes the following items [1] to [7]. [1] A polarizing film comprising polyvinyl alcohol (A), at least one boron-containing compound (B) selected from the group consisting of a monoboronic acid represented by the following formula (I) and a compound capable of being converted to the monoboronic acid in the presence of water, and boric acid (C), wherein the boron element concentration (α) derived from the boron-containing compound (B) in an area from the center to 1 μm outward in the thickness direction is 0.1 to 3 atomic %, the boron element concentration (β) derived from the boric acid (C) in an area from the center to 1 μm outward in the thickness direction is 0.1 to 8 atomic %, and the ratio (α / β) of the concentration (α) to the concentration (β) is 0.1 or more;
[0011] [ka]
[0012] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond. [2] R 1 The polarizing film according to [1], wherein [3] R 1 the polarizing film according to [1] or [2], wherein [4]R 1 [5] The polarizing film according to any one of [1] to [4], which has a transmittance of 42.0% or more and a polarization degree of 99.85% or more; [6] The polarizing film according to any one of [1] to [5], which has a contraction force in the absorption axis direction per width of 1.5 cm and thickness of 13 μm when maintained at 80° C. for 4 hours of less than 12 N; [7] A method for producing a polarizing film according to any one of [1] to [6], comprising a dyeing treatment of dyeing a polyvinyl alcohol film with a dichroic dye and a stretching treatment of uniaxially stretching the film, the method further comprising a treatment of immersing the film in an aqueous solution of a boron-containing compound (B) having a concentration of 0.2 to 5 mass% at a temperature of 20 to 70°C. Effect of the Invention
[0013] According to the present invention, it is possible to provide a polarizing film which has a small shrinkage force at high temperatures and excellent optical performance, and a method for producing the same. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view of a polarizing film of the present invention cut in the vertical direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Polarizing film> The polarizing film of the present invention comprises polyvinyl alcohol (A), at least one boron-containing compound (B) selected from the group consisting of a monoboronic acid represented by the following formula (I) and a compound that can be converted to the monoboronic acid in the presence of water, and boric acid (C), wherein the boron element concentration (α) derived from the boron-containing compound (B) in the range from the center to 1 μm outward in the thickness direction is 0.1 to 3 atomic %, the boron element concentration (β) derived from the boric acid (C) in the range from the center to 1 μm outward in the thickness direction is 0.1 to 8 atomic %, and the ratio (α / β) of the concentration (α) to the concentration (β) is 0.1 or more.
[0016] [ka]
[0017] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.
[0018] FIG. 1 is a cross-sectional view of the polarizing film of the present invention cut in the vertical direction. The central portion 3 in the thickness direction of the polarizing film is a range from the center 1 in the thickness direction of the polarizing film to 1 μm in both directions on the surface portion 2 side of the polarizing film, and is the range indicated by diagonal lines in FIG. 1. In the polarizing film of the present invention, the boron element concentration (α) derived from the boron-containing compound (B) in the range from the center in the thickness direction of the polarizing film to 1 μm outward, the boron element concentration (β) derived from the boron acid (C) in the range from the center in the thickness direction of the polarizing film to 1 μm outward, and the ratio (α / β) of the concentration (α) to the concentration (β) are in specific ranges. When a polarizing film crosslinked with boric acid (C) is immersed in an aqueous solution of the boron-containing compound (B), the substitution reaction between the boron-containing compound (B) and the boric acid (C) proceeds from the surface portion of the polarizing film. The above α, β and their ratio α / β being within a specific range indicate that the substitution reaction between the boron-containing compound (B) and boric acid (C) has progressed to the center of the polarized film in the thickness direction, thereby resulting in a polarized film with small shrinkage force at high temperatures and excellent optical performance.
[0019] The boron element concentration (α) derived from the boron-containing compound (B) in the range from the center of the polarizing film in the thickness direction to 1 μm outward must be 0.1 to 3 atomic %. If the boron element concentration (α) is less than 0.1 atomic %, a sufficient amount of the boron-containing compound (B) is not present up to the center of the polarizing film in the thickness direction, and the effect of reducing the contraction force is reduced. On the other hand, if the boron element concentration (α) exceeds 3 atomic %, it is considered that there is no effect on the optical performance and contraction force of the polarizing film, but the time of the fixation treatment in which the film is immersed in an aqueous solution of the boron-containing compound (B) described later becomes long, which may reduce the productivity of the polarizing film.
[0020] The boron element concentration (β) derived from boric acid (C) in the range from the center of the polarizing film in the thickness direction to 1 μm outward must be 0.1 to 8 atomic %. If the boron element concentration (β) is less than 0.1 atomic %, the amount of boric acid (C) in the center of the polarizing film in the thickness direction is insufficient, causing the orientation state of the PVA molecular chains in the polarizing film to become disturbed, resulting in reduced optical performance. On the other hand, if the boron element concentration (β) exceeds 8 atomic %, there will be an excess of PVA molecular chains oriented by boric acid crosslinking in the center of the polarizing film in the thickness direction, which may result in an insufficient effect on reducing the contraction force.
[0021] The ratio (α / β) of the boron element concentration (α) derived from the boron-containing compound (B) to the boron element concentration (β) derived from the boron acid (C) in the range from the center of the polarizing film to 1 μm outward in the thickness direction must be 0.1 or more. If the boron element concentration ratio (α / β) is less than 0.1, it is estimated that the amount of boric acid (C) is large and the amount of the boron-containing compound (B) is small in the center of the thickness direction of the polarizing film. In this case, since there is an excess of PVA molecular chains oriented by boric acid crosslinking in the center of the thickness direction of the polarizing film, there is a risk that the contraction force will not decrease. On the other hand, even if the boron element concentration ratio (α / β) exceeds 3, it is considered that there is no influence on the optical performance and contraction force of the polarizing film, but the time of the fixation treatment of immersing in an aqueous solution of the boron-containing compound (B) described later becomes long, and the productivity of the polarizing film may decrease, so that the boron element concentration ratio (α / β) is preferably 3 or less.
[0022] The boron element concentration (α) and the boron element concentration (β) in the polarizing film can be determined using a gas cluster ion beam gun-equipped X-ray photoelectron spectrometer (GCIB XPS), specifically, by the method described in the examples below.
[0023] The thickness of the polarizing film is preferably 5 to 30 μm. If the thickness is too thin, stretching breaks tend to occur easily during uniaxial stretching to produce the polarizing film. The thickness is preferably 10 μm or more. On the other hand, if the thickness is too thick, stretching unevenness tends to occur easily during uniaxial stretching to produce the polarizing film, and the shrinkage force of the produced polarizing film tends to be large.
[0024] The boron-containing compound (B) in the present invention is at least one selected from the group consisting of monoboronic acids represented by the following formula (I) and compounds that can be converted to the monoboronic acids in the presence of water. 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.
[0025] [ka]
[0026] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.
[0027] A monoboronic acid is a compound represented by the above formula (I), and has one boronic acid group [-B(OH)2] in one molecule. The boronic acid group has a structure in which a boron atom to which two hydroxyl groups are bonded is bonded to a carbon atom. In the compound represented by formula (I), R 1 and the boronic acid group are connected by a boron-carbon bond. In boric acid [B(OH)3], the boron atom is bonded to three hydroxyl groups, whereas the boronic acid group has a boron-carbon bond. A representative example of a boron-containing group that can be converted to a boronic acid group in the presence of water is the boronic acid ester group described below, but is not limited thereto.
[0028] The hydroxyl group in the boronic acid group contained in the monoboronic acid can form an ester with an alcohol, just like the hydroxyl group in boric acid. The following formula (II) shows a boronic acid with one molecule of alcohol (R 2 In this case, when the boronic acid group is bonded to the hydroxyl group of PVA (A), R in formula (II) is a monoboronic acid monoester. 2 is a PVA chain, and a carbon-containing group is bonded to the PVA chain via a boron atom.
[0029] [ka]
[0030] The following formula (III) represents a compound in which two molecules of alcohol (R 2 This is an example of a monoboronic acid diester in which the boronic acid group is reacted with the hydroxyl group of PVA. Here, when the boronic acid group is bonded to the hydroxyl group of PVA, the two R 2 are both PVA chains.
[0031] [ka]
[0032] Monoboronic acid has two hydroxyl groups that can react with the hydroxyl groups of PVA to form esters, resulting in moderate cross-linking of the PVA chains. This cross-linking is heat stable, so the shrinkage force of the polarizing film at high temperatures is reduced. This reduces the warping of LCD panels using polarizing films at high temperatures. In addition, moderate cross-linking of the PVA chains improves the orientation of the PVA chains, which is thought to improve the optical performance of the polarizing film.
[0033] In formula (I), R 1 R is a monovalent aliphatic group having 1 to 20 carbon atoms. 1 By setting R to an appropriate length, the solubility of the boron-containing compound (B) in water and the reactivity with the hydroxyl group of PVA can be controlled. 1The number of carbon atoms in R is preferably 10 or less, more preferably 6 or less, and even more preferably 5 or less. On the other hand, from the viewpoint of a particularly excellent balance between the optical performance and the shrinkage force of the polarizing film, R 1 The number of carbon atoms is preferably 2 or more, and more preferably 3 or more.
[0034] In formula (I), R 1 is a monovalent aliphatic group, R 1 and the boronic acid group are connected by a boron-carbon bond. 1 R may be a saturated or unsaturated aliphatic group, but the former is preferred. 1 By being a saturated aliphatic group, coloration of the resulting polarizing film is suppressed and durability is improved. 1 By being a saturated aliphatic group, the orientation of the dichroic dye is improved, and the optical performance is further improved. Note that an unsaturated aliphatic group is an aliphatic group having a structure containing multiple bonds with a bond order of 2 or more, such as a carbon-carbon double bond, a carbon-carbon triple bond, a carbon-oxygen double bond, a carbon-nitrogen double bond, a nitrogen-nitrogen double bond, or a carbon-sulfur double bond, and a saturated aliphatic group is an aliphatic group having only a single bond structure. 1Examples of monoboronic acids in which is a saturated aliphatic group include methylboronic acid, ethylboronic acid, propylboronic acid, butylboronic acid, pentylboronic acid, hexylboronic acid, heptylboronic acid, octylboronic acid, nonylboronic acid, decanylboronic acid, undecanylboronic acid, dodecanylboronic acid, tridecylboronic acid, tetradecanylboronic acid, pentadecanylboronic acid, hexadecanylboronic acid, heptadecanylboronic acid, octadecanylboronic acid, nonadecanylboronic acid, icosanylboronic acid and isomers thereof, cyclopropylboronic acid, cyclobutylboronic acid, ethylboronic acid, propylboronic acid, butylboronic acid, pentylboronic acid, hex ...butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butyl Boronic acid, cyclopentylboronic acid, cyclohexylboronic acid, cycloheptylboronic acid, cyclooctylboronic acid, cyclononylboronic acid, cyclodecanylboronic acid, cycloundecanylboronic acid, cyclododecanylboronic acid, cyclotridecanylboronic acid, cyclotetradecanylboronic acid, cyclopentadecanylboronic acid, cyclohexadecanylboronic acid, cycloheptadecanylboronic acid, cyclooctadecanylboronic acid, cyclononadecanylboronic acid, cycloicosanylboronic acid and their isomers, 2-oxa-propylboronic acid, 2-oxo ... Subbutylboronic acid, 2-oxa-hexylboronic acid, 2-oxa-heptylboronic acid, 2-oxa-octylboronic acid, 2-oxa-nonylboronic acid, 2-oxa-decanylboronic acid, 2-oxa-undecanylboronic acid, 2-oxa-dodecanylboronic acid, 2-oxa-tridecanylboronic acid, 2-oxa-tetradecanylboronic acid, 2-oxa-pentadecanylboronic acid, 2-oxa-hexadecanylboronic acid, 2-oxa-heptadecanylboronic acid, 2-oxa-octadecanylboronic acid, 2-oxa-nonadecanylboronic acid, 2-oxa- Icosanylboronic acid and its isomers, 2-aza-propylboronic acid, 2-aza-butylboronic acid, 2-aza-hexylboronic acid, 2-aza-heptylboronic acid, 2-aza-octylboronic acid, 2-aza-nonylboronic acid, 2-aza-decanylboronic acid, 2-aza-undecanylboronic acid, 2-aza-dodecanylboronic acid, 2-aza-tridecanylboronic acid, 2-aza-tetradecanylboronic acid, 2-aza-pentadecanylboronic acid, 2-aza-hexadecanylboronic acid, 2-aza-heptadecanylboronic acid, 2-aza-octadecanylboronic acid,2-Aza-nonadecanylboronic acid, 2-aza-icosanylboronic acid and their isomers, 2-phospha-propylboronic acid, 2-phospha-butylboronic acid, 2-phospha-hexylboronic acid, 2-phospha-heptylboronic acid, 2-phospha-octylboronic acid, 2-phospha-nonylboronic acid, 2-phospha-decanylboronic acid, 2-phospha-undecanylboronic acid, 2-phospha-dodecanylboronic acid, 2-phospha-tridecanylboronic acid, 2-phospha-tetradecanylboronic acid, 2-phospha-pentadecanylboronic acid, 2-phospha-hexadecanylboronic acid, 2-phospha-heptadecanylboronic acid, 2-phospha-octadecanylboronic acid, 2-phospha-nonadecanylboronic acid Examples of boronic acid include 2-thia-propylboronic acid, 2-thia-butylboronic acid, 2-thia-hexylboronic acid, 2-thia-heptylboronic acid, 2-thia-octylboronic acid, 2-thia-nonylboronic acid, 2-thia-decanylboronic acid, 2-thia-undecanylboronic acid, 2-thia-dodecanylboronic acid, 2-thia-tridecanylboronic acid, 2-thia-tetradecanylboronic acid, 2-thia-pentadecanylboronic acid, 2-thia-hexadecanylboronic acid, 2-thia-heptadecanylboronic acid, 2-thia-octadecanylboronic acid, 2-thia-nonadecanylboronic acid, 2-thia-icosanylboronic acid and isomers thereof. In addition, examples of the compound that can be converted to the monoboronic acid in the presence of water include salts of the monoboronic acid.
[0035] R 1 may be an aliphatic hydrocarbon group or may contain heteroatoms such as oxygen, nitrogen, sulfur, and halogen. 1 is preferably an aliphatic hydrocarbon group that does not contain a heteroatom. The aliphatic hydrocarbon group is preferably a straight-chain aliphatic hydrocarbon group that does not have a branch. This improves the adsorption to the polarizing film, and enhances the effect of improving the optical performance. 1Specific examples of the boronic acid in which is a straight-chain aliphatic hydrocarbon group include methylboronic acid, ethylboronic acid, n-propylboronic acid, n-butylboronic acid, n-pentylboronic acid, n-hexylboronic acid, n-heptylboronic acid, n-octylboronic acid, n-nonylboronic acid, n-decylboronic acid, n-undecanylboronic acid, n-dodecanylboronic acid, n-tridecanylboronic acid, n-tetradecanylboronic acid, n-pentadecanylboronic acid, n-hexadecanylboronic acid, n-heptadecanylboronic acid, n-octadecanylboronic acid, n-nonadecanylboronic acid, and n-icosanylboronic acid. Examples of compounds that can be converted to the exemplified boronic acids in the presence of water include salts of the boronic acids.
[0036] Specifically, the monoboronic acid represented by the above formula (I) is particularly preferably ethylboronic acid, n-propylboronic acid, n-butylboronic acid, or n-pentylboronic acid. In addition, examples of compounds that can be converted to these exemplified boronic acids in the presence of water include salts of the boronic acids.
[0037] <PVA(A)> The PVA (A) in the present invention is a polymer having a vinyl alcohol unit (-CH2-CH(OH)-) as a main structural unit.
[0038] The degree of polymerization of the PVA (A) contained in the polarizing film of the present invention is preferably within the range of 1,500 to 6,000, more preferably within the range of 1,800 to 5,000, and even more preferably within the range of 2,000 to 4,000. When the degree of polymerization is 1,500 or more, the durability of the polarizing film obtained by uniaxially stretching the film can be improved. On the other hand, when the degree of polymerization is 6,000 or less, an increase in production costs and poor processability during film formation can be suppressed. In this specification, the degree of polymerization of the PVA (A) means the average degree of polymerization measured in accordance with the description of JIS K6726-1994.
[0039] The saponification degree of the PVA (A) contained in the polarizing film of the present invention is preferably 95 mol% or more, more preferably 96 mol% or more, and even more preferably 98 mol% or more, from the viewpoint of the water resistance of the polarizing film obtained by uniaxially stretching the film. In this specification, the saponification degree of the PVA refers to the ratio (mol%) of the number of moles of the vinyl alcohol unit to the total number of moles of the structural unit (typically a vinyl ester unit) that can be converted to a vinyl alcohol unit (-CH2-CH(OH)-) by saponification that the PVA has. The saponification degree can be measured according to the description of JIS K6726-1994.
[0040] The method for producing the PVA (A) used in the present invention is not particularly limited. For example, a method of converting vinyl ester units of polyvinyl ester obtained by polymerizing vinyl ester monomers into vinyl alcohol units can be mentioned. The vinyl ester monomer used for producing the PVA (A) is not particularly limited, but examples thereof include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, and vinyl benzoate. From an economical viewpoint, vinyl acetate is preferred.
[0041] The PVA (A) used in the present invention may be a vinyl ester copolymer obtained by copolymerizing a vinyl ester monomer with another monomer copolymerizable therewith, in which the vinyl ester units are converted into vinyl alcohol units. Examples of other monomers copolymerizable with the vinyl ester monomer include α-olefins having 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutene; (meth)acrylic acid or a salt thereof; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, diacetone(meth)acrylamide, (meth)acrylamidopropanesulfonic acid or a salt thereof, and (meth)acrylamidopropyldimethylamine or a salt thereof. salts thereof, (meth)acrylamide derivatives such as N-methylol (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; vinyl cyanides such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters, or acid anhydrides; itaconic acid or its salts, esters, or acid anhydrides; vinyl silyl compounds such as vinyltrimethoxysilane; and unsaturated sulfonic acids. The vinyl ester copolymers described above may have structural units derived from one or more of the other monomers described above.The other monomers can be used by having them present in the reaction vessel beforehand when the vinyl ester monomer is subjected to the polymerization reaction, or by adding them to the reaction vessel during the progress of the polymerization reaction, etc. From the viewpoint of optical performance, the content of units derived from other monomers is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 2 mol % or less, based on the number of moles of all structural units constituting PVA (A).
[0042] Among the monomers copolymerizable with the vinyl ester monomer, ethylene is preferred because it improves stretchability and allows stretching at a higher temperature, reducing the occurrence of problems such as breakage during production of the polarized film, and further improving the productivity of the polarized film. When PVA (A) contains ethylene units, the content of the ethylene units is preferably 1 to 10 mol%, more preferably 2 to 6 mol%, based on the number of moles of all structural units constituting PVA (A), from the viewpoints of the stretchability and the temperature at which the film can be stretched as described above.
[0043] The PVA film used in the production of the polarizing film of the present invention may contain a plasticizer in addition to the above-mentioned PVA (A). Preferred plasticizers include polyhydric alcohols, and specific examples thereof include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane. Furthermore, one or more of these plasticizers may be contained. Among these, glycerin is preferred from the viewpoint of improving the stretchability.
[0044] The content of the plasticizer in the PVA film used in the production of the polarizing film of the present invention is preferably within the range of 1 to 20 parts by mass, more preferably within the range of 3 to 17 parts by mass, and even more preferably within the range of 5 to 15 parts by mass, relative to 100 parts by mass of PVA (A). When the content is 1 part by mass or more, the stretchability of the film is improved. On the other hand, when the content is 20 parts by mass or less, it is possible to prevent the film from becoming too flexible and the handling properties from being deteriorated.
[0045] The PVA film used in the production of the polarizing film of the present invention may further contain additives other than PVA (A) and plasticizers, such as fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, UV absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, antifoaming agents, deodorants, extenders, peeling agents, release agents, reinforcing agents, crosslinking agents, fungicides, preservatives, and crystallization rate retarders, as necessary. The content of other additives in the PVA film is usually 10% by mass or less, and preferably 5% by mass or less.
[0046] The swelling degree of the PVA film used in the production of the polarizing film of the present invention is preferably within the range of 160 to 240%, more preferably within the range of 170 to 230%, and particularly preferably within the range of 180 to 220%. When the swelling degree is 160% or more, it is possible to suppress the crystallization from proceeding excessively, and it is possible to stably stretch to a high ratio. On the other hand, when the swelling degree is 240% or less, dissolution during stretching is suppressed, and it is possible to stretch even under higher temperature conditions. The swelling degree of the PVA film is measured by the method described in the examples.
[0047] <Method of manufacturing polarizing film> The thickness of the PVA film used in the production of the polarizing film of the present invention is not particularly limited, but is generally 1 to 100 μm, preferably 5 to 60 μm, and particularly preferably 10 to 45 μm. If the PVA film is too thin, it tends to be easily cut during uniaxial stretching to produce the polarizing film. If the PVA film is too thick, it tends to be easily stretched unevenly during uniaxial stretching to produce the polarizing film, and the shrinkage force of the produced polarizing film tends to be large.
[0048] The width of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited and can be determined depending on the application of the polarizing film to be manufactured. In recent years, the screen size of liquid crystal televisions and liquid crystal monitors has been increasing, so that the width of the PVA film used in the manufacture of the polarizing film is 3 m or more, which is suitable for these applications. On the other hand, if the width of the PVA film used in the manufacture of the polarizing film is too large, it is likely to be difficult to uniformly perform uniaxial stretching when the polarizing film is manufactured using a practical device, so the width of the PVA film used in the manufacture of the polarizing film is preferably 10 m or less.
[0049] The method for producing the PVA film used in the production of the polarizing film of the present invention is not particularly limited, and a production method that makes the thickness and width of the film uniform after film production is preferably adopted. For example, the polarizing film can be produced using a film-forming stock solution in which PVA (A) and, if necessary, one or more of the plasticizer, the other additives, and the surfactant described below are dissolved in a liquid medium, or a film-forming stock solution in which PVA (A) and, if necessary, one or more of the plasticizer, other additives, surfactant, and liquid medium are contained and PVA (A) is melted. When the film-forming stock solution contains at least one of the plasticizer, other additives, and surfactant, it is preferable that these components are uniformly mixed.
[0050] Examples of the liquid medium used to prepare the film-forming solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc., and one or more of these may be used. Among these, water is preferred from the viewpoints of environmental load and recovery.
[0051] The volatile fraction of the film-forming solution (the content ratio of volatile components such as liquid medium removed by volatilization or evaporation during film formation in the film-forming solution) varies depending on the film-forming method and film-forming conditions, but is generally preferably in the range of 50 to 95% by mass, more preferably in the range of 55 to 90% by mass. When the volatile fraction of the film-forming solution is 50% by mass or more, the viscosity of the film-forming solution does not become too high, filtration and degassing during preparation of the film-forming solution are smoothly performed, and a film with few foreign matter and defects is easily produced. On the other hand, when the volatile fraction of the film-forming solution is 95% by mass or less, the concentration of the film-forming solution does not become too low, and industrial film production is easy.
[0052] The film-forming solution preferably contains a surfactant. By containing a surfactant, the film-forming property is improved, the occurrence of unevenness in the thickness of the film is suppressed, and the film is easily peeled off from the metal roll or belt used in film formation. When a PVA film is produced from a film-forming solution containing a surfactant, the film may contain a surfactant. The type of the surfactant is not particularly limited, but an anionic surfactant or a nonionic surfactant is preferable from the viewpoint of peelability from the metal roll or belt.
[0053] Suitable anionic surfactants include, for example, carboxylic acid types such as potassium laurate; sulfate ester types such as polyoxyethylene lauryl ether sulfate and octyl sulfate; and sulfonic acid types such as dodecylbenzenesulfonate.
[0054] Suitable examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether.
[0055] These surfactants can be used alone or in combination of two or more.
[0056] When the film-forming solution contains a surfactant, the content is preferably within the range of 0.01 to 0.5 parts by mass, more preferably within the range of 0.02 to 0.3 parts by mass, and particularly preferably within the range of 0.05 to 0.2 parts by mass, relative to 100 parts by mass of PVA (A) contained in the film-forming solution. When the content is 0.01 parts by mass or more, the film-forming property and the peeling property are further improved. On the other hand, when the content is 0.5 parts by mass or less, it is possible to suppress the surfactant from bleeding out onto the surface of the PVA film, causing blocking and reducing the handleability.
[0057] Examples of the film-forming method when forming a PVA film using the film-forming solution include a cast film-forming method, an extrusion film-forming method, a wet film-forming method, and a gel film-forming method. These film-forming methods may be used alone or in combination of two or more. Among these film-forming methods, the cast film-forming method and the extrusion film-forming method are preferred because they can produce a PVA film that is uniform in thickness and width and has good physical properties and is used to manufacture a polarizing film. The formed PVA film can be dried or heat-treated as necessary.
[0058] As a specific example of a method for producing the PVA film used in the production of the polarizing film of the present invention, for example, a method is preferably adopted industrially in which the above film-forming solution is uniformly discharged or cast onto the peripheral surface of a rotating heated first roll (or belt) located at the most upstream side using a T-shaped slit die, a hopper plate, an I-die, a lip coater die, etc., volatile components are evaporated from one side of the film discharged or cast onto the peripheral surface of the first roll (or belt) to dry it, and then the film is further dried on the peripheral surface of one or more rotating heated rolls arranged downstream, or further dried by passing through a hot air dryer, and then wound up by a winding device. Drying by a heated roll and drying by a hot air dryer may be carried out in appropriate combination. A multi-layer PVA film may also be produced by forming a layer made of PVA (A) on one side of a substrate film composed of a single resin layer.
[0059] The method for producing the polarizing film of the present invention is not particularly limited. A suitable production method is a method for producing a polarizing film including a dyeing process for dyeing a PVA film with a dichroic dye and a stretching process for uniaxially stretching the film, and a process for immersing the film in an aqueous solution of a boron-containing compound (B). In addition to the dyeing process and the uniaxial stretching process, the PVA film may be subjected to a swelling process, a boric acid crosslinking process, a fixing process, a washing process, a drying process, a heat treatment, or the like, if necessary. In this case, the order of each process such as the swelling process, the dyeing process, the boric acid crosslinking process, the uniaxial stretching process, and the fixing process is not particularly limited, and two or more processes may be performed simultaneously. Each process may also be performed two or more times.
[0060] The swelling treatment can be carried out by immersing the PVA film in water. The temperature of the water in which the film is immersed is preferably within the range of 20 to 40°C, more preferably within the range of 22 to 38°C, and even more preferably within the range of 25 to 35°C. The time for immersion in water is, for example, preferably within the range of 0.1 to 5 minutes, and more preferably within the range of 0.2 to 3 minutes. The water in which the film is immersed is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and a hydrophilic medium.
[0061] The dyeing treatment can be carried out by contacting the PVA film with a dichroic dye. As the dichroic dye, an iodine-based dye or a dichroic dye is generally used. The dyeing treatment may be carried out at any stage before, during, or after the uniaxial stretching treatment. The dyeing treatment is generally carried out by immersing the PVA film in a solution (particularly an aqueous solution) containing iodine-potassium iodide as a dye bath, or in a solution (particularly an aqueous solution) containing a plurality of dichroic dyes. The concentration of iodine in the dye bath is preferably within a range of 0.01 to 0.5% by mass, and the concentration of potassium iodide is preferably within a range of 0.01 to 10% by mass. The temperature of the dye bath is preferably 20 to 50°C, particularly 25 to 40°C. The suitable dyeing time is 0.2 to 5 minutes. When a dichroic dye is used, the dichroic dye is preferably an aqueous dye. The dye concentration in the dye bath is preferably 0.001 to 10% by mass. Also, dyeing assistants may be used as necessary, and inorganic salts such as sodium sulfate, surfactants, etc. may be used. When sodium sulfate is used, 0.1 to 10 mass% is preferable. Specific dichroic dyes include CI Direct Yellow 28, CI Direct Orange 39, CI Direct Yellow 12, CI Direct Yellow 44, CI Direct Orange 26, CI Direct Orange 71, CI Direct Orange 107, CI Direct Red 2, CI Direct Red 31, CI Direct Red 79, CI Direct Red 81, CI Direct Red 247, CI Direct Green 80, and CI Direct Green 59, but dichroic dyes developed for polarizing plate manufacturing are preferable.
[0062] By subjecting the PVA film to boric acid crosslinking treatment, the PVA molecular chains in the PVA film are crosslinked, improving the orientation of the PVA molecular chains. As a result, the orientation of the dichroic dye adsorbed to the PVA film is improved, and the optical performance of the resulting polarizing film is improved. From this viewpoint, it is more preferable to perform the boric acid crosslinking treatment after the dyeing treatment and before the stretching treatment. The boric acid crosslinking treatment can be performed by immersing the PVA film in an aqueous solution containing a boric acid crosslinking agent. As the boric acid crosslinking agent, one or more of boron-containing inorganic compounds such as boric acid and borax and other borate salts can be used, and from the viewpoint of ease of handling, the boric acid crosslinking agent is preferably boric acid. The concentration of the boric acid crosslinking agent in the aqueous solution containing the boric acid crosslinking agent is preferably 1 to 10% by mass, more preferably 2 to 7% by mass. By having the concentration of the boric acid crosslinking agent be 1 to 10% by mass, sufficient stretchability can be maintained. If the concentration of the boric acid crosslinking agent exceeds 10% by mass, crosslinking may proceed excessively, resulting in a decrease in stretchability, or the PVA molecular chain may be excessively oriented, resulting in an increase in contraction force, which is not preferable. If the concentration of the boric acid crosslinking agent is less than 1% by mass, the orientation of the dichroic dye adsorbed to the PVA film may not be sufficiently improved, and the optical performance of the resulting polarizing film may not be sufficiently improved, which is not preferable. The aqueous solution containing the boric acid crosslinking agent may contain an auxiliary such as potassium iodide. The temperature of the aqueous solution containing the boric acid crosslinking agent is preferably 20 to 50°C, and particularly preferably 25 to 40°C. By setting the temperature at 20 to 50°C, boric acid crosslinking can be efficiently performed.
[0063] Apart from the uniaxial stretching treatment described later, the PVA film may be stretched (pre-stretched) during or between each of the above-mentioned treatments. In this way, the total stretching ratio (a ratio obtained by multiplying the stretching ratios in each treatment) of the pre-stretching performed before the uniaxial stretching treatment is preferably 1.5 times or more, more preferably 2.0 times or more, and even more preferably 2.5 times or more, based on the original length of the raw material PVA film before stretching, from the viewpoint of the optical performance of the resulting polarizing film. On the other hand, the total stretching ratio is preferably 4.0 times or less, and more preferably 3.5 times or less. The stretching ratio in the swelling treatment is preferably 1.05 to 2.5 times. The stretching ratio in the dyeing treatment is preferably 1.1 to 2.5 times. The stretching ratio in the boric acid crosslinking treatment is preferably 1.1 to 2.5.
[0064] The uniaxial stretching treatment may be performed by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, the PVA film is stretched in an aqueous solution. The PVA film can also be stretched in the above-mentioned dye bath or in an aqueous boric acid solution. In the case of the dry stretching method, the uniaxial stretching treatment may be performed at room temperature, or may be performed while heating, or the uniaxial stretching treatment may be performed in air using the PVA film after absorbing water. Among these, the wet stretching method is preferred, and it is more preferred to perform the uniaxial stretching treatment in an aqueous solution containing boric acid. The concentration of boric acid in the aqueous boric acid solution is preferably within the range of 0.5 to 6% by mass, more preferably within the range of 1 to 5% by mass. The aqueous boric acid solution may also contain potassium iodide, and the concentration thereof is preferably within the range of 0.01 to 10% by mass. The stretching temperature in the uniaxial stretching treatment is preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher. On the other hand, the stretching temperature is preferably 90°C or less, more preferably 80°C or less, and even more preferably 70°C or less. The stretching ratio in the uniaxial stretching process is preferably 2.0 to 4.0 times. From the viewpoint of the optical performance of the resulting polarized film, the stretching ratio is more preferably 2.2 times or more. On the other hand, the stretching ratio is more preferably 3.5 times or less. From the viewpoint of the optical performance of the resulting polarized film, the total stretching ratio before the fixing process described later is preferably 5 times or more, more preferably 5.5 times or more, based on the original length of the raw material PVA film before stretching. There is no particular upper limit to the stretching ratio, but the stretching ratio is preferably 8 times or less.
[0065] When a long PVA film is uniaxially stretched, the direction of the uniaxial stretching is not particularly limited, and uniaxial stretching in the long direction, uniaxial stretching in the transverse direction, or so-called oblique stretching can be used, but uniaxial stretching in the long direction is preferred because it produces a polarizing film with excellent optical performance. The uniaxial stretching in the long direction can be performed by using a stretching device equipped with multiple rolls parallel to each other and changing the peripheral speed between the rolls. On the other hand, the transverse uniaxial stretching can be performed using a tenter-type stretching machine.
[0066] In the production of polarizing films, it is preferable to carry out a fixing treatment after the uniaxial stretching treatment in order to strengthen the adsorption of the dichroic dye (iodine-based dye, etc.) to the PVA film. As the fixing treatment bath used for the fixing treatment, an aqueous solution containing a boron-containing compound (B) is preferably used. In addition, boric acid, an iodine compound, a metal compound, etc. may be further added to the fixing treatment bath as necessary. In order to accelerate the substitution reaction between the boron-containing compound (B) and boric acid (C) at the center in the thickness direction of the polarizing film, it is preferable that the fixing treatment bath does not substantially contain boric acid. The temperature of the fixing treatment bath is preferably 10 to 80°C. The stretching ratio in the fixing treatment is preferably 1.3 times or less, more preferably 1.2 times or less, and even more preferably less than 1.1 times.
[0067] The boron-containing compound (B) may be adsorbed to the polarizing film in any of the steps of dyeing, boric acid crosslinking, uniaxial stretching, and fixing, but it is particularly preferable to adsorb it during the fixing process after the uniaxial stretching process, since this suppresses the cutting of the PVA film during the uniaxial stretching process. In addition, not only one type of boron-containing compound (B) but also two or more types may be used in combination. From the viewpoint of allowing the substitution reaction between the boron-containing compound (B) and boric acid (C) to proceed to the center in the thickness direction of the polarizing film, the concentration of the aqueous solution of the boron-containing compound (B) needs to be 0.2 to 5 mass%. If the concentration of the boron-containing compound (B) in the aqueous solution is lower than 0.2 mass%, the adsorption of the boron-containing compound (B) to the surface of the polarizing film becomes slow, and it is more preferable that the concentration is 0.4 mass% or more, and even more preferable that the concentration is 0.6 mass% or more. On the other hand, if the concentration of the boron-containing compound (B) in the aqueous solution is higher than 5.0% by mass, the boron-containing compound (B) is excessively adsorbed on the surface of the polarizing film, and the substitution reaction between the boron-containing compound (B) and boric acid (C) is difficult to proceed. In addition, there is a risk of the boron-containing compound (B) depositing on the surface of the polarizing film. The concentration of the boron-containing compound (B) is more preferably 4.0% by mass or less, even more preferably 2.0% by mass or less, and particularly preferably 1.0% by mass or less.
[0068] In addition, the aqueous solution containing the boron-containing compound (B) preferably contains an iodide auxiliary such as potassium iodide from the viewpoint of improving optical performance, and the concentration of the iodide is preferably 0.5 to 15 mass%. The temperature of the aqueous solution containing the boron-containing compound (B) needs to be 20 to 70°C. If the temperature of the aqueous solution containing the boron-containing compound (B) is less than 20°C, it becomes difficult to allow the substitution reaction of substituting boric acid in the polarizing film with boronic acid to proceed to the center in the thickness direction of the polarizing film. In addition, the boron-containing compound (B) may precipitate in the aqueous solution containing the boron-containing compound (B). The temperature of the aqueous solution containing the boron-containing compound (B) is preferably 23°C or higher, more preferably 25°C or higher. On the other hand, if the temperature of the aqueous solution containing the boron-containing compound (B) is too high, it becomes difficult to easily produce a polarizing film industrially under relatively mild conditions. The temperature of the aqueous solution containing the boron-containing compound (B) is preferably 60°C or lower, more preferably 40°C or lower. The time for immersion in the aqueous solution containing the boron-containing compound (B) is preferably from 5 to 400 seconds.
[0069] As a method for producing a polarizing film by adsorbing the boron-containing compound (B) to the polarizing film during the fixing treatment, a method in which a swelling treatment, a uniaxial stretching treatment, and a fixing treatment are performed in this order, a method in which a swelling treatment, a boric acid crosslinking treatment, a uniaxial stretching treatment, and a fixing treatment are performed in this order, and a method in which a swelling treatment, a uniaxial stretching treatment, a fixing treatment, and a boric acid crosslinking treatment are performed in this order are preferred. After performing these treatments, one or more treatments selected from a washing treatment, a drying treatment, and a heat treatment may be further performed as necessary.
[0070] The cleaning treatment is generally performed by immersing the PVA film in distilled water, pure water, an aqueous solution, or the like. In this case, from the viewpoint of improving optical performance, it is preferable to use an aqueous solution containing an iodide such as potassium iodide as an auxiliary, and the concentration of the iodide is preferably 0.5 to 10 mass %. The temperature of the aqueous solution in the cleaning treatment is generally 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. From the economic viewpoint, it is not preferable that the temperature of the aqueous solution is too low, and if the temperature of the aqueous solution is too high, the optical performance may be reduced.
[0071] The conditions for the drying treatment are not particularly limited, but drying is preferably carried out at a temperature within a range of 30 to 150° C., particularly within a range of 50 to 130° C. Drying at a temperature within a range of 30 to 150° C. tends to produce a polarizing film with excellent dimensional stability.
[0072] By carrying out a heat treatment after the drying treatment, a polarizing film with even better dimensional stability can be obtained. Here, the heat treatment refers to a treatment in which a polarizing film with a moisture content of 5% or less after the drying treatment is further heated to improve the dimensional stability of the polarizing film. The conditions for the heat treatment are not particularly limited, but it is preferable to carry out the heat treatment within the range of 60°C to 150°C, particularly within the range of 70°C to 150°C. If the temperature is lower than 60°C, the dimensional stabilization effect by the heat treatment is insufficient, and if the temperature is higher than 150°C, the polarizing film may be significantly discolored red.
[0073] The polarizing film of the present invention thus obtained preferably has a transmittance of 42.0% or more and a polarization degree of 99.85% or more. If the transmittance of the polarizing film is less than 42.0%, the brightness of the resulting LCD may be insufficient. The transmittance is more preferably 43.0% or more, and even more preferably 43.5% or more. Meanwhile, the transmittance is usually 45% or less. Furthermore, if the polarization degree of the polarizing film is 99.85% or more, an LCD panel with high image quality can be obtained. The transmittance and polarization degree of the polarizing film are measured by the method described in the examples below.
[0074] The thus obtained polarizing film of the present invention preferably has a contraction force in the absorption axis direction per 1.5 cm width and 13 μm thickness of less than 12 N when held at 80° C. for 4 hours. If the contraction force of the polarizing film is 12 N or more, when the LCD is enlarged, the LCD may be easily warped due to heat generated by the screen, and light may leak from the edges. The contraction force of the polarizing film is measured by the method described in the examples.
[0075] The polarizing film of the present invention is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on either or both sides of the film. Examples of the protective film include cellulose triacetate (TAC) film, cellulose acetate butyrate (CAB) film, acrylic film, and polyester film. Examples of adhesives for lamination include PVA adhesives and UV-curable adhesives.
[0076] The polarizing plate obtained as described above may be laminated with a retardation film, a viewing angle improving film, a brightness improving film, etc. In addition, the polarizing plate may be coated with an acrylic or other adhesive, and then laminated with a glass substrate to be used as a part of an LCD. EXAMPLES
[0077] The present invention will be described in detail with reference to the following examples, but the present invention is not limited to these examples. The evaluation methods used in the following examples and comparative examples are shown below.
[0078] <Optical performance of polarizing film> A rectangular sample of 4 cm in the length direction × 2 cm in the width direction was taken from the center of the polarizing film in the width direction and length direction, and the parallel transmittance and crossed Nicol transmittance of the polarizing film were measured using a spectrophotometer V-7100 (manufactured by JASCO Corporation) with an integrating sphere and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan-Taylor polarizer. Here, the measurement wavelength range was set to 380 nm to 780 nm, and the transmittance when the vibration direction of the polarized light incident on the polarizing film through the Glan-Taylor polarizer is parallel to the transmission axis of the polarizing film was defined as the parallel transmittance, and the transmittance when it is perpendicular to the transmission axis of the polarizing film was defined as the crossed Nicol transmittance. Thereafter, using a "Polarizing Film Evaluation Program" (manufactured by JASCO Corporation), luminosity correction was performed in the visible light region with a C light source and a 2° field of view using the above-mentioned parallel transmittance and crossed Nicol transmittance in accordance with JIS Z 8722 (measurement method for object color), and the single transmittance and degree of polarization of the polarizing film were calculated, and these two values were obtained as the optical properties of the polarizing film.
[0079] <Contraction force of polarizing film> The shrinkage force was measured using an autograph "AG-X" with a thermostat manufactured by Shimadzu Corporation and a video extensometer "TRViewX120S". Since the absorption axis direction and the length direction (drawing axis direction) of the polarizing film are substantially the same, the shrinkage force in the absorption axis direction of the polarizing film was obtained by measuring the tension in the length direction (drawing axis direction). For the measurement, a polarizing film (15 cm in the length direction (drawing axis direction) and 1.5 cm in the width direction) conditioned at 20°C / 20%RH for 18 hours was attached to a chuck (chuck interval: 5 cm), and simultaneously with the start of tension, the temperature of the thermostat was raised to 80°C. The polarizing film was pulled at a speed of 1 mm / min, and when the tension reached 2 N, the pulling was stopped, and the tension was measured until 4 hours later in that state. At this time, since the distance between the chucks changes due to thermal expansion, a scale seal was attached to the chucks, and the measurement was performed while correcting so that the distance between the chucks remained constant by the amount that the scale seal attached to the chucks moved using the video extensometer "TR VieWX120S". In addition, when a minimum value of the tension occurred within the initial stage of the measurement (within 10 minutes from the start of the measurement), the minimum value of the tension was subtracted from the measured value of the tension after 4 hours, and the difference was taken as the shrinkage force in the drawing axis direction of the polarizing film.
[0080] <Degree of swelling of PVA film> The PVA film was cut into 5 cm × 10 cm and immersed in 1000 mL of distilled water at 30°C for 30 minutes. Then, the PVA film was taken out, and the moisture on the surface of the PVA film was wiped off with filter paper, and the mass of the PVA film after immersion (mass H) was measured. Then, the PVA film was placed in a dryer at 105°C and dried for 16 hours, and the mass of the PVA film after drying (mass I) was measured. The degree of swelling of the PVA film was calculated by substituting the values of mass H and mass I into the following formula (1). Degree of swelling (%) = (mass H / mass I) × 100 (1)
[0081] <Boron element concentration (α) and boron element concentration (β)> The boron element concentration derived from the boron-containing compound (B) in the polarizing film was measured using an X-ray photoelectron spectrometer equipped with a gas cluster ion beam gun (ULVAC-PHI Inc.: PHI5000 VersaProbe II) (GCIB-XPS). The polarizing film was conditioned for more than 16 hours at approximately 23°C / 40%RH for the measurement. Sputtering was performed in an area of 1mm x 1mm while neutralizing under the conditions of sputter ion source Ar2500+, acceleration voltage 10keV, and current value 30nA, and X-ray photoelectron spectroscopy measurement (XPS measurement) was performed. XPS measurement was performed using monochromated Al as the X-ray source, with an X-ray spot diameter of 200μm, X-ray output of 15kV, 50W, and five elements were selected as detection elements: carbon, boron, oxygen, iodine, and potassium. When a dichroic dye is used as the dichroic dye, elements such as nitrogen and sulfur contained in the dichroic dye must also be appropriately selected as detection elements. Next, the boron element concentration (a, atomic %) at each depth in the thickness direction of the polarizing film was calculated using the analysis software "MultiPak" (ULVAC-PHI, Inc.) based on 284.8 eV, which is the bond energy of C-C and C-H bonds. After that, for the XPS spectrum at each depth, the bond energy due to boron in boric acid (C) and the bond energy due to boron in the boron-containing compound (B) were appropriately set, and peak separation was performed by the least squares method using the pseudo-Voigt function using the spreadsheet software "Microsoft Excel 2010" (Microsoft Corporation). Note that a linear function calculated from the average value of the intensity of the XPS spectrum from 187 to 189 eV and the average value of the XPS spectrum from 195 to 197 was used as the baseline. In this manner, the peak area (b, %) of boron derived from the boron-containing compound (B) relative to the total of boron derived from boric acid (C) and boron derived from the boron-containing compound (B) was calculated, and the peak area (b, %) was substituted into the following calculation formula (2) to calculate the boron element concentration derived from the boron-containing compound (B) at each depth. Boron element concentration (atomic %) from boron-containing compounds (B) = a × b × 10 -2 (2)
[0082] The bond energy due to boron in the boron-containing compound (B) varies depending on the structure of the compound. Therefore, it is necessary to set the bond energy appropriately depending on the type of boron-containing compound (B). For example, when the boron-containing compound (B) is n-propylboronic acid, the bond energy is around 191.5 eV. In addition, when performing peak separation by the least squares method using the pseudo-Voigt function, the Lorentz function ratio of boric acid is set to 0.241, and 2 1 / 2 ×σ was set to 0.916. The Lorentz function ratio and half-width of the boron-containing compound (B) also change depending on the structure of the compound. Therefore, the Lorentz function ratio and 2 1 / 2 × σ must be set appropriately. When the boron-containing compound (B) is n-propylboronic acid, the Lorentz function ratio is 0.000, 2 1 / 2 ×σ was set to 0.769.
[0083] Using this method, the boron element concentration (α, atomic %) derived from the boron-containing compound (B) within 1 μm from the center of the polarizing film in the thickness direction was determined. Also, the boron element concentration (β, atomic %) derived from boric acid within 1 μm from the center of the polarizing film in the thickness direction was determined.
[0084] <Example 1> An aqueous PVA solution was prepared containing 100 parts by mass of PVA (saponification degree 99.9%, polymerization degree 2400), 10 parts by mass of glycerin as a plasticizer, and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, with a PVA content of 10% by mass. The aqueous PVA solution was dried on a metal roll at 80°C to obtain a film, which was then heat-treated in a hot air dryer (120°C) for 10 minutes to obtain a PVA film with a thickness of 30 μm and a swelling degree of 200%.
[0085] A sample of 5 cm wide x 9 cm long was cut from the center of the width direction of the obtained PVA film so that a range of 5 cm wide x 5 cm long could be uniaxially stretched. This sample was immersed in pure water at 30 ° C for 30 seconds and uniaxially stretched 1.1 times in the length direction to perform swelling treatment. Next, it was immersed in an aqueous solution (dyeing treatment bath) at 30 ° C containing 0.035 mass % iodine and 3.5 mass % potassium iodide for 60 seconds and uniaxially stretched 2.2 times (total 2.4 times) in the length direction to adsorb iodine. Next, it was immersed in an aqueous solution (boric acid crosslinking treatment bath) at 30 ° C containing 3.0 mass % boric acid and 3 mass % potassium iodide and uniaxially stretched 1.1 times (total 2.7 times) in the length direction. Further, the film was immersed in a 60°C aqueous solution (stretching bath) containing 4.0% by mass of boric acid and 6% by mass of potassium iodide, and uniaxially stretched in the length direction to a total of 6.0 times. After the uniaxial stretching treatment, the film was immersed for 100 seconds in a 30°C aqueous solution (fixing bath) containing 0.7% by mass of n-propylboronic acid as a boron-containing compound (B) and 2 to 5% by mass of potassium iodide. In the fixing treatment, the PVA film was not stretched (stretching ratio 1.0 times). Finally, the film was dried at 60°C for 240 seconds to produce a polarizing film (thickness 13 μm).
[0086] The XPS spectrum of the polarizing film was measured and analyzed, and the boron element concentration (α) derived from the boron-containing compound (B) in the range of 1 μm from the center in the thickness direction of the polarizing film was 1.4 atomic %, and the boron element concentration (β) derived from boric acid in the range of 1 μm from the center in the thickness direction of the polarizing film was 1.5 atomic %. The optical properties and contraction force of the polarizing film were evaluated by the above-mentioned method, and the transmittance was 44.18%, the polarization degree was 99.89%, and the contraction force was 0.6 N.
[0087] <Examples 2 to 4> Polarizing films were produced in the same manner as in Example 1, except that the immersion time in the fixing treatment bath and the aqueous solution concentration were changed as shown in Table 1, and each measurement and evaluation were carried out.
[0088] <Comparative Example 1> This is an example of a polarizing film that does not contain a boron-containing compound (B). A polarizing film was produced in the same manner as in Example 1, except that an aqueous solution (temperature 30°C) containing 2% by mass of potassium iodide was used as the fixing treatment bath, and the time of immersion in the fixing treatment bath was changed to 20 seconds, and each measurement and evaluation were performed. The boron element concentration (β) derived from boric acid (C) was low, and the contraction force of the polarizing film was low at 6.4 N, but the polarization degree was insufficient at less than 99.85%.
[0089] <Comparative Example 2> This is an example of a polarizing film that does not contain a boron-containing compound (B). A polarizing film was produced in the same manner as in Example 1, except that an aqueous solution (temperature: 30°C) containing 2% by mass of potassium iodide was used as the fixing treatment bath, and the time of immersion in the fixing treatment bath was changed to 5 seconds, and each measurement and evaluation were performed. At this time, the contraction force of the polarizing film exceeded 12 N, and the contraction force was not sufficiently reduced.
[0090] In Examples 2 to 4 and Comparative Example 1, iodine was adsorbed by uniaxially stretching the film lengthwise to 2.2 times its original size (total of 2.4 times) while immersing the film in an aqueous solution (dyeing bath) (temperature: 30° C.) containing 100 parts by mass of potassium iodide per 1 part by mass of iodine for 60 seconds, as in Example 1. The concentrations of iodine and potassium iodide in the dyeing bath were adjusted so that the transmittance of the polarizing film after drying would be 43.8 to 44.2%.
[0091] [Table 1]
[0092] As shown in Table 1, the polarizing films of Examples 1 to 4 have a small shrinkage force at high temperatures and are excellent in optical performance.
[0093] As shown in the examples, the polarizing film of the present invention has high optical performance and low shrinkage force, and therefore can meet the recent demand for thinner and higher definition electronic devices. [Explanation of symbols]
[0094] 1. Center of the polarizing film in the thickness direction 2. Surface of polarizing film 3. Center of polarizing film thickness
Claims
1. A polarizing film comprising polyvinyl alcohol (A), at least one boron-containing compound (B) selected from the group consisting of a monoboronic acid represented by the following formula (I) and a compound capable of being converted to the monoboronic acid in the presence of water, and boric acid (C), wherein the boron element concentration (α) derived from the boron-containing compound (B) in a range from the center to 1 μm outward in the thickness direction is 0.1 to 3 atomic %, the boron element concentration (β) derived from the boric acid (C) in a range from the center to 1 μm outward in the thickness direction is 0.1 to 8 atomic %, and the ratio (α / β) of the concentration (α) to the concentration (β) is 0.1 or more and 3 or less, and the polarizing film has a contraction force of less than 12 N in the absorption axis direction per width of 1.5 cm and thickness of 13 μm when maintained at 80° C. for 4 hours. 【Chemistry 1】 [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.
2. R 1 The polarizing film of claim 1 , wherein is a saturated aliphatic group.
3. R 1 The polarizing film according to claim 1 or 2, wherein is a linear aliphatic hydrocarbon group.
4. R 1 The polarizing film according to any one of claims 1 to 3, wherein the number of carbon atoms is 2 to 5.
5. 5. The polarizing film according to claim 1, which has a transmittance of 42.0% or more and a polarization degree of 99.85% or more.
6. The method for producing a polarizing film according to any one of claims 1 to 5, comprising a dyeing treatment of dyeing a polyvinyl alcohol film with a dichroic dye and a stretching treatment of uniaxially stretching the film, further comprising a treatment of immersing the film in an aqueous solution of a boron-containing compound (B) having a concentration of 0.2 to 2.0 mass% at a temperature of 20 to 70°C.
Citation Information
Patent Citations
Polarization film and method for producing the same
JP2019015926A
Crosslinking agent for preparing a polarizer and method of preparing a polarizer using the same
KR1020140075154A
Polarizer and manufacturing method thereof
KR1020150001276A
Process for Preparing Polarizer
KR1020150052777A
Process for Preparing Polarizer
KR1020160054229A